THE ROLE OF PHYSICS IN BIOLOGY - Saydaliyeva Shaxlo Samikovna; Maxmudov Mannon Hasanovich (Web of Journals Publishing, 2024)
Physics plays a key role in the formation of biochemistry, molecular biology, molecular genetics, genetic engineering and biotechnology. The main biological processes that take place in a living organism are carried out through physical processes of the genetic code, the transmission of hereditary characters from generation to generation, the transfer of substance ions from membranes, photosynthesis and energetic processes. This article provides information about the diversity of energy metabolism in living organisms.